6(3p+3)-6=-5

Simple and best practice solution for 6(3p+3)-6=-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(3p+3)-6=-5 equation:


Simplifying
6(3p + 3) + -6 = -5

Reorder the terms:
6(3 + 3p) + -6 = -5
(3 * 6 + 3p * 6) + -6 = -5
(18 + 18p) + -6 = -5

Reorder the terms:
18 + -6 + 18p = -5

Combine like terms: 18 + -6 = 12
12 + 18p = -5

Solving
12 + 18p = -5

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-12' to each side of the equation.
12 + -12 + 18p = -5 + -12

Combine like terms: 12 + -12 = 0
0 + 18p = -5 + -12
18p = -5 + -12

Combine like terms: -5 + -12 = -17
18p = -17

Divide each side by '18'.
p = -0.9444444444

Simplifying
p = -0.9444444444

See similar equations:

| 4(-8+12)=-26-32x | | w-15=22 | | 4x+3(x-5)=5x-6 | | w^2+3w+4w^2+1=4w^2-5 | | 3xsquared+5x=2x+7x | | 8x^2-5=-149 | | 3(3x+2)-4=3 | | 4c-6=4-3c | | -108=6(6x-6) | | 4x=5+45 | | 6x+10=50 | | 6ax+7b=1cx+d | | 10x-14=6x+22 | | 6+4k=6(8k+1) | | -97=3(6n+8)+5 | | -58=7.25c | | 3x+-50=-11 | | 11=-d+17 | | x^4+5=6*x^2 | | x^2+1x+9=0 | | 3(v+2)-8=31 | | 36=6-3x | | g(x)=2x^2+6 | | y=9(0)+5 | | -8=2n-4-6n | | 11x-2=57 | | 45=b-30 | | 2y+1=8+2y | | y=60+20x | | y=20x+60 | | 6-(2k+5)=10 | | 2(Y-6)+2Y=-8 |

Equations solver categories